The use of Instagram to improve students' EFL Writing - Noordi, Asy Syiffa Fatata Rahima; Triana, Novita; Fadilla, Raisa (Syntax Literate, 2024)
Good communication makes it easier for us to connect with the community and other individuals with various backgrounds. Language is also a catalyst for us to understand ourselves and others, and is the key that opens the window of our world’s view. Every aspect on human life is very dependent on the proficiency of language skills. The goal of this paper was to see how the use of Instagram improved the students’ EFL writing ability. The method used to conduct this paper was Systematic Literature Review. There are 10 articles from various journals that are analyzed and synthetized to extract the data from. Based on the authors finding, the use of Instagram brought forth positive improvement on the students’ writing ability, as well as their motivation in language acquisition study.